The role of hypoxia-induced modulation of alveolar epithelial Na+-transport in hypoxemia at high altitude: $hEmel Baloglu, Gabriel Nonnenmacher, Anna Seleninova, Lena Berg, Kalpana Velineni, Ezgi Ermis-Kaya and Heimo Mairbäurl - Baloğlu, Emel; Nonnenmacher, Gabriel; Seleninova, Anna; Berg, Lena; Velineni, Kalpana; Ermis-Kaya, Ezgi; Mairbäurl, Heimo (Pulmonary circulation, 2020)
Reabsorption of excess alveolar fluid is driven by vectorial Na+-transport across alveolar epithelium, which protects from alveolar flooding and facilitates gas...
Im Titel ist "+" in Na+-transport hochgestellt
Gesehen am 05.11.2020